2011
DOI: 10.1016/j.mambio.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Food habits of Japanese deer in an evergreen forest: Litter-feeding deer

Abstract: We observed the feeding behaviors of wild Japanese sika deer (Cervus nippon yakushimae) in a warm temperate broad-leaved evergreen forest of the island of Yakushima using the focal animal sampling Deer also fed on animal matters as minor food items, such as the feces of monkeys and raccoon dogs, bones of deer and monkeys, and bird carcasses. Animal matters constituted 0.3-1.6% of the seasonal diet.Sympatric monkeys supplied food to deer as a result of their daily activities. Monkey-supplied foods 2 comprised 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Deer in the study area were well habituated (Agetsuma et al 2011) and researchers could follow them and observe their behavior at close quarters. On May 20, 2015, we followed three female deer and collected their fecal pellets just after defecation.…”
Section: Study Area and Fecal Sample Collectionmentioning
confidence: 99%
“…Deer in the study area were well habituated (Agetsuma et al 2011) and researchers could follow them and observe their behavior at close quarters. On May 20, 2015, we followed three female deer and collected their fecal pellets just after defecation.…”
Section: Study Area and Fecal Sample Collectionmentioning
confidence: 99%
“…Furthermore, it is sometimes uncertain whether the locations in which the ungulates were shot to obtain the rumens are coincident with their foraging grounds and the environmental availability of food items eaten (Bee et al ). Browsing marks are difficult to consistently quantify across various food types (Wam and Hjeljord ), and if ungulates frequently feed on forest litter, such as fallen leaves and fruits (Gayot et al , Soumya et al , Agetsuma et al , Tsuji et al ), there are often no traces of consumption. Some of these difficulties can be resolved by conducting feeding experiments in captivity and semi‐captivity.…”
mentioning
confidence: 99%
“…Direct observation of the feeding behavior of wild animals in their natural habitats has the potential to avoid most of the methodological problems that are inherent in indirect dietary analyses and food selection experiments in captivity as discussed above, provided the plant species, plant parts, and even the condition of food plants that are eaten can be sufficiently identified (Agetsuma et al ). Direct observation also provides information of potential foods that are available to specific animals when they select food items.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that the deer shifted to litter fall as main food items. Agetsuma et al (2011) observed deer foraging behavior around HNYM and reported that 75% of the deer diet consisted of forest litter, such as fallen leaves, flowers or fruits. Thus, it seems likely that the dependence on litter fall as the diet increased along with increasing deer density in the forests where deer density was higher than 20 deer/km 2 , which resulted in the nonlinear relationship between deer density and deer herbivory.…”
Section: Nonlinear Relationship Between Deer Density and Herbivorymentioning
confidence: 99%